Effectiveness of cognitive remediation in subjects with major depressive disorder: A multicenter randomized controlled study in a real-world setting - Stefano Barlati; Gabriele Nibbio; Antonello Bellomo; Bernardo Carpiniello; Cristina Colombo; Serafino De Giorgi; Giacomo Deste; Giuseppe Maina; Giovanni Martinotti; Alfonso Tortorella; Gabriele Di Salvo; Mario Luciano; et al. (European Psychiatry)
Abstract